Analysis of Clinical Features of Non-steroidal Anti-inflammatory Drugs Induced Kounis Syndrome - Wang, Chunjiang; Fang, Weijin; Song, Liying; Deng, Zhenzhen; Li, Zuojun; Sun, Linli (Frontiers in Cardiovascular Medicine, 2022)
Background Current knowledge of Kounis syndrome induced by non-steroidal anti-inflammatory drugs (NSAIDs) is based on case reports. This study aimed to investigate the clinical features of Kounis syndrome. Methods Case reports of the NSAIDs-induced Kounis syndrome were analyzed by searching Chinese and English databases from 1 January 1950 to 31 January 2022. Results The median age of the 45 included patients (28 women) was 51 years (20–80 years). NSAIDs that were the most frequently involved were diclofenac (26.7%, 12/45), metamizole (15.6%, 7/45), and aspirin (13.3%, 6/45). Kounis syndrome occurred mainly within 30 min after administration, with a maximum latency of 1 month. Chest pain (75.6%, 34/45), dyspnea (33.3%, 15/45), and allergic reactions (44.4%, 20/45) were the most common clinical manifestations. Thirty patients (66.7%) had an ST-segment elevation on the electrocardiogram. Echocardiogram and coronary angiography showed abnormalities in 21 patients (75%, 21/28) and 15 patients (37.5%, 15/40). Forty-four patients (97.8%) had a good prognosis after treatment with steroids, antihistamines, and vasodilators. Conclusion The possibility of Kounis syndrome should be considered in the presence of coronary artery disease symptoms when taking NSAIDs. Kounis syndrome can be life-threatening. It is essential to identify and treat Kounis syndrome correctly.